Unmanned aerial vehicles mitigate human–elephant conflict on the borders of Tanzanian Parks: a case study. Issue 3 (9th November 2016) - Hahn, Nathan; Mwakatobe, Angela; Konuche, Jonathan; de Souza, Nadia; Keyyu, Julius; Goss, Marc; Chang'a, Alex; Palminteri, Suzanne; Dinerstein, Eric; Olson, David
Abstract: Protected areas across the range of the African savannah elephant Loxodonta africana are increasingly being surrounded and isolated by agriculture and human settlements. Conflicts between people and crop-raiding elephants regularly lead to direct reprisals and diminish community support for conservation. We report on field trials in northern Tanzania that employed a new, humane way for wildlife managers to move elephants away from conflict zones, from distances of > 100 m, thereby enhancing the safety of wildlife managers, farmers and elephants. We deployed 10 unmanned aerial vehicles (drones) piloted by five trained teams of wildlife managers in the Tarangire–Manyara and Serengeti ecosystems. Game Scouts deployed the drones opportunistically during crop-raiding events at the peak of the maize ripening period in 2015 and 2016. In 100% of trials (n = 51) elephants responded to the presence of a drone by departing rapidly from crop fields (n = 38) and settlements (n = 13). The cost of five teams responsible for 617 km 2 in Tarangire–Manyara was estimated to be USD 15, 520 for 1 year, and all drones remained operational for the duration of the study. The initial success of this tool warrants further testing of the utility of small unmanned aerial vehicles as part of the toolbox for wildlife managers and communities dealing with high levels of conflict with wildlife.